Technology assessment in the homegarden systems - Allan Thomas (Department of Agricultural Extension, College of Horticulture, 2004)
Homegardens of Kerala presents a traditional agroforestry system designed to meet the food, fodder, fuel wood and timber requirement of the farm households and to generate supplementary income through the sale of surplus (Salam and Sreekumar, 1991). The homegarden system has its unique structural configuration and cropping patterns. The structural and functional diversity of this farming system makes it a unique one. It is the predominant type of agricultural production system in the state of Kerala (Shehana et al., 1994).